Perceptual expertise bridging brain and behavior - Gauthier, Isabel; Tarr, Michael J.; Bub, Daniel (New York ; Oxford : Oxford University Press, 2010)
This work presents a comprehensive survey of perceptual expertise in visual object recognition, and introduces a novel collaborative model, codified as the 'Perceptual Expertise Network' (PEN).
Description based on print version record.
Includes bibliographical references and index.
Keywords: Visual perception; Face perception; Categorization (Psychology)